Assessment of Echinococcus multilocularis surveillance data 2012–2013 submitted by Norway in the context of Commission Regulation (EU) No 1152/2011. (27th February 2015) - ,; ,
Abstract: This report provides an analysis and critical assessment of the sampling strategy, the data collected, and the detection methods used in the Norwegian 2012–2013 E. multilocularis surveillance campaigns and reported in the context of Regulation (EU) No 1152/2011 regarding preventive health measures for the control of E . multilocularis infection in dogs. The surveillance aims at detecting the parasite, if present, in mainland Norway. The Norwegian surveillance reports were assessed by checking the description of the surveillance system for completeness against the relevant elements that need to be addressed in assessing the quality of E . multilocularis surveillance reports in the context of Regulation (EU) No 1152/2011. The data reported on individual samples were assessed using the raw data submitted by Norway via the EFSA Data Collection Framework (DCF). Descriptive statistics were calculated to check whether the requirements of Regulation (EU) No 1152/2011 had been fulfilled. The E . multilocularis ‐specific surveillance programme aimed at detecting the parasite, if present in mainland Norway, has not detected E. multilocularis through the surveillance activities performed in 2012 and 2013. Under the assumption of unbiased representative sampling and considering the sensitivity of the tests applied, Norway has fulfilled the requirement of Regulation (EU) No 1152/2011 to the effect that the surveillance activities should detect a prevalence of E . multilocularis of 1 % or less at a confidence level of at least 0.95 in 2012, but not in 2013.